Transplant Fictions - Russell, Emily (Palgrave Macmillan, 2019)
1. Introduction – 2. Corpse to Cadaver: From Body Snatching to Body Worlds – 3. Making the Lifelike Corpse – 4. Mortal Signs: Transplantation and the Invention of Brain Death – 5. “The Gift of Life”: Sentiment and the Family – 6. Murdering Hands and Mad Doctors: The Horrors of Organ Exchange – 7. Kidneyville: Organ Exchange at the Margins – 8. Conclusion: Speculative Medicine, Speculative Fictions Removing an organ from one (typically dead) body and placing it in another living body challenges our most foundational ideas about boundaries between self and other, individual and social identity, life and death, health and illness. But despite these transgressions, organ transplant is a celebrated and relatively common procedure. Transplant Fictions brings together a diverse set of cultural representations to understand how we have overcome the profound ideological violations represented by organ exchange in order to reimagine the concept and practice as technological and moral victories. From the plots of horror stories and sci-fi novels to sentimental romances and feel-good media reports of stranger donation, this cultural study offers a nuanced portrait of the conceptual journey of organ exchange from strange and terrible to the “gift of life.”
10.1007/978-3-030-12135-8
Keywords: Literary History; Literature-History and criticism; Fiction; British literature